Necrotizing Fasciitis caused by Streptococcus pyogenes: A case report and literature review of disease diagnosis and management - Aziz, Hassan A (Archives of Community Medicine and Public Health, 2017)
Background: A 55-year-old male presented to the emergency room at a local hospital complaining of chest discomfort and severe left elbow pain. Case Presentation: Erythema and symptoms of peripheral neuropathy were evident in the left hand. The patient reported recent trauma to his left elbow; however a radiograph of the left arm was unremarkable for fracture. After being admitted to the intensive care unit for observation, he developed worsening pain out of proportion and progressive decreased sensation in his left hand. Diagnosis: Initially, left arm compartment syndrome was suspected and treated accordingly. After surgical intervention, the patient’s subsequent symptoms and preliminary blood culture results revealed Gram positive cocci in chains, indicating necrotizing fasciitis. The isolate was identified as group A beta-hemolytic Streptococcus (GABS). Treatment and Follow-up: Broad-spectrum antibiotics given at outset were extended with additional antibiotics. Treatment consisted of five separate surgeries involving extensive debridement of necrotic tissue amounting to approximately 55 to 65 percent of the patient’s body surface area. The patient was eventually released to a burn center for skin grafting and wound closure and in less than three months, he expired.